1988
DOI: 10.1111/j.1445-2197.1988.tb06241.x
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in the First Three Years of Life

Abstract: Appendicitis is the first 3 years of life is uncommon and most cases are perforated at laparotomy. Case records at the Adelaide Children's Hospital were reviewed over a 12‐year period. The findings were that acute appendicitis in this age group is commonly associated with respiratory symptoms and diarrhoea, the appendix was gangrenous or perforated in 92% of cases, and there was a significant delay in diagnosis. It is concluded that full evaluation of any child of this age with fever, vomiting, abdominal pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…The mean age of the study population was 10 years or older in most of these publications. Acute appendicitis is the most frequent reason for laparotomy in children; however, it is relatively rare in babies and very young children and less than 5 % of all pediatric appendicitis is diagnosed in children 5 years and younger [10][11][12][13][14]. The spectrum of differential diagnoses in children with acute abdominal pain is wide, ranging from emergent surgical conditions, various non-surgical and infectious conditions, and self-limiting conditions.…”
Section: Introductionmentioning
confidence: 97%
“…The mean age of the study population was 10 years or older in most of these publications. Acute appendicitis is the most frequent reason for laparotomy in children; however, it is relatively rare in babies and very young children and less than 5 % of all pediatric appendicitis is diagnosed in children 5 years and younger [10][11][12][13][14]. The spectrum of differential diagnoses in children with acute abdominal pain is wide, ranging from emergent surgical conditions, various non-surgical and infectious conditions, and self-limiting conditions.…”
Section: Introductionmentioning
confidence: 97%
“…The appeal of this hypothesis is that it provides an explanation for certain epidemiological characteristics of appendicitis. The epidemiology of acute appendicitis shows a rising incidence accompanies increasing industrialisation (Barker et al, 1988). This is believed to be because as increasing industrialisation and improved socio-economic conditions arise there is a concomitant improvement in hygiene.…”
Section: The Pathophysiological Mechanisms Of Acute Appendicitismentioning
confidence: 99%
“…In the 2 to 5 age group, the pain tends to be more localised which is in contrast to the children of ages 2 and younger where the abdominal pain tends to be more diffuse. Localised tenderness has been reported to be present in less that 50% in this age group (Barker & Davey, 1988;Horwitz et al, 1997). Patients in this age group or even younger tend to also exhibit lethargy, abdominal distension, diarrhoea and fever.…”
Section: Appendicitis At the Extremes Of Agementioning
confidence: 99%
“…24 The high perforation rates in the series of Grosfeld and Barker (94% and 92%, respectively) could be related to the significant delay in diagnosis and appendectomy. 2,23 Conventional open appendectomy has generally been accepted as the immediate treatment for appendicitis. In perforated appendicitis, many institutions have adopted a more vigorous approach, consisting of immediate appendectomy, irrigation of peritoneal cavity, transperitoneal drainage through the wound and a 10-day course of intravenous antibiotics.…”
Section: 9-mentioning
confidence: 99%
“…Perforation rates in infants have been reported between 55% and 94% by several authors. 23,[9][10][11][12]23 Byrne et al showed that the duration of symptoms influenced the outcome of appendicitis.If symptoms were present from 0 to 11 hours, 13% of patients perforated, while 12 to 13 hours' duration produced a 23% perforation rate and if symptoms persisted for more than 72 hours, up to 100% perforated. 24 The high perforation rates in the series of Grosfeld and Barker (94% and 92%, respectively) could be related to the significant delay in diagnosis and appendectomy.…”
mentioning
confidence: 99%